Problematics of Mahārah al-Qirā’ah (Reading Skill) in Arabic Language Learning - Nurul Mustofa; Rahmat Hidayat; Rohiyanata; Wira Pahrias; Zidani Ilman Maulana; Fathurrahman; Sirajut Talibin; Rahmat Zainuri (Formad English Foundation NTB Jakarta, 2026)
This study investigates the problematics of maharah al-qirā’ah (Arabic reading skills) in Arabic language learning by examining the major difficulties experienced by learners, the contributing linguistic and instructional factors, and the pedagogical implications. Reading skill plays a central role in accessing Arabic texts, yet many learners continue to struggle with accuracy, fluency, and comprehension. The research employed a descriptive qualitative approach using library research. Data were collected from scholarly books, peer-reviewed journal articles, and relevant academic sources published within the last decade. The materials were analyzed through qualitative content analysis to identify recurring themes related to reading difficulties, causal factors, and instructional solutions. The findings indicate that learners face multidimensional challenges, including limited vocabulary mastery, weak understanding of grammatical structures (nahwu and sharaf), difficulty recognizing morphological patterns, phonological inaccuracy, low reading fluency, and problems in identifying main ideas and making contextual inferences. These difficulties are influenced by linguistic complexity, teacher-centered instructional practices, limited strategy-based teaching, inadequate learning media, mismatched curriculum materials, and minimal exposure to Arabic outside the classroom. The study concludes that improving Arabic reading competence requires integrated strategies that combine phonological training, morphological awareness, functional grammar instruction, explicit reading strategy development, interactive pedagogy, and supportive learning environments. The findings contribute to a more comprehensive understanding of Arabic reading instruction and provide practical insights for educators and curriculum developers.